Pengaruh Pengalaman Kerja, Audit Tenure, Dan Fee Audit Terhadap Kinerja Auditor Syariah - Yulia Dwi Safitri; Cris Kuntadi (STIKes Ibnu Sina Ajibarang, 2024)
This article reviews the factors that influence the performance of sharia auditors, namely work experience, audit tenure and audit fees. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The research methods used are qualitative methods and library research. The results of this literature review article are: 1) work experience influences the performance of sharia auditors; 2) audit tenure has no effect on the performance of sharia auditors; and 3) audit fees influence the performance of Sharia auditors. From the results of this research, it is hoped that future researchers can add variables that are considered to influence the performance of Sharia auditors.